Short and practical enantioselective synthesis of linezolid and eperezolid via proline-catalyzed asymmetric alpha-aminooxylation - Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of the antibacterials, linezolid (U-100766), and eperezolid (U-100592) using D-proline-catalyzed asymmetric alpha-aminooxylation of aldehydes as the key step is described here. This is the first report on the enantioselective synthesis of linezolid and eperezolid using asymmetric catalysis. (c) 2006 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of the antiepileptic agent, levetiracetam based on proline-catalyzed asymmetric alpha-aminooxylation - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of a new antiepileptic drug, levetiracetam is described, in high optical purity (> 99.5% ee), using proline-catalyzed alpha-aminooxylation of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of (-)-bestatin via L-proline-catalyzed alpha-amination of an aldehyde - George, Shyla; Suryavanshi, Gurunath S.; Sudalai, Arumugam (Tetrahedron Letters, 2008)
A short and high yielding enantioselective synthesis of (-)-bestatin, a naturally occurring aminopeptidase inhibitor, is described Via L-proline-catalyzed asymmetric alpha-amination of 3-phenylpropionaldehyde as the key reaction. The methodology also involves a Pd-catalyzed intramolecular cyclization of an allylic acetate giving a trans-oxazoline in a highly diastereoselective manner (dr > 14:1). (C) 2008 Elsevier Ltd. All rights reserved.

Short enantioselective synthesis of (+)-L-733,060 via Shi epoxidation of a homoallylic carboxylate - Emmanuvel, Lourdusamy; Sudalai, Arumugam (Tetrahedron Letters, 2008)
A short and efficient enantioselective synthesis of (+)-L-733,060 in 92% ee via Shi epoxidation of a homoallylic carboxylate is described. Johnson-Claisen rearrangement was employed to obtain the required carbon backbone, whilst intramolecular reductive O-to-N-ring expansion of a delta-azidolactone was used in the construction of the piperidine moiety. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-aminoalcohols; 3; 3-sigmatropic rearrangement; asymmetric epoxidation; Lactone

Short enantioselective synthesis of guggultetrol, a naturally occurring lipid - George, Shyla; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2010)
An enantioselective synthesis of the naturally occurring lipid, guggultetrol, is described with an overall yield of 24% starting from commercially available 1-pentadecanol in ten linear steps. The key chiral-inducing steps include a Sharpless asymmetric epoxidation of allylic alcohol and a dihydroxylation of an alpha,beta-unsaturated ester. (C) 2010 Elsevier Ltd. All rights reserved.

Simple and efficient synthesis of isocoumarins and alkylidenephthalides from 3-(1-hydroxycarbethoxy/alkyl)phthalides with a DEAD/PPh3/TBHP system - Gadakh, Sunita K.; Sudalai, Arumugam (RSC Advances, 2014)
A facile and novel approach to the synthesis of 3-carbethoxy-isocoumarins and 3-alkylidenephthalides is described. The methodology employs DEAD/PPh3/TBHP as the reagent system proceeding through unprecedented 1,2-shift intramolecular ring expansion or simple elimination depending upon substituents present on 3-substituted phthalides, with broader substrate scope. This strategy is amply demonstrated in the short synthesis of bioactive molecules such as cytogenin and (Z)-3-butylidene-7-hydroxy-5-methoxyphthalide.

Short enantioselective synthesis of ephedrine, amphetamine and their analogues via two stereocentered Co(III)-catalyzed hydrolytic kinetic resolution of racemic syn-benzyloxy epoxide - Lalwani, Komal G.; Sudalai, Arumugam (Tetrahedron Letters, 2015)
An efficient route for the synthesis of 6 drugs belonging to phenethylamine and amphetamine classes in excellent overall yields and high optical purity has been described. The strategy involves introduction of stereogenic centers by means of two-stereocentered Co(III)-catalyzed hydrolytic kinetic resolution (HKR) of racemic syn-benzyloxy epoxide followed by Pd-catalyzed regioselective cationic hydrogenation of amino alcohols as the key reactions. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Amphetamine; Cationic hydrogenation; Hydrolytic kinetic resolution; Phenethylamine; Stereogenic centers

Sodium periodate mediated oxidative transformations in organic synthesis - Sudalai, Arumugam; Khenkin, Alexander; Neumann, Ronny (Organic & Biomolecular Chemistry, 2015)
The investigation of new oxidative transformations for the synthesis of carbon-heteroatom and heteroatom-heteroatom bonds is of fundamental importance in the synthesis of numerous bioactive molecules and fine chemicals. In this context, NaIO4, an exciting reagent, has attracted increasing attention enabling the development of these unprecedented oxidative transformations that are difficult to achieve otherwise. Thus, NaIO4 has been successfully explored as a versatile oxidant for a variety of fundamental organic transformations such as C-H activation, oxidative functionalization of alkenes and other interesting oxidative transformations and its application in the synthesis of bioactive natural products. This review summarizes recent developments in this area with NaIO4 as a versatile oxidant and brings out many challenges that still remain elusive for the future.

Studies toward the total synthesis of (+)-neopeltolide using N-heterocyclic carbene-catalyzed oxo-acyloxylation/reductive oxa-Michael addition strategy - Reddi, Rambabu N.; Sudalai, Arumugam; Jo, Changbum (Bulletin of the Korean Chemical Society, 2022)
This article describes a concise synthesis of two important fragments (tetrahydropyran [THP] and ketone moieties) of the cytotoxic macrolide (+)-neopeltolide in 10 long linear steps in enantiomerically pure form. Asymmetric Keck allylation to install the required C11 and C13 stereocenters, N-heterocyclic carbene (NHC)-catalyzed oxoacyloxylation to functionalize alkenes, and reductive oxa-Michael addition to construct 2,6-difunctionalized THP unit intramolecularly are the important steps in synthetic efforts. Finally, Keck asymmetric allylation and Lewis acid-catalyzed diastereoselective allylation of the aldehyde were sequentially employed to establish the stereocenters at C11 and C13 positions, respectively.
Keywords: (+)-neopeltolide; Keck allylation; Macrolide; NHC-catalyzed oxoacyloxylation; reductive oxa-Michael addition